FRI0100 Sustained development of cardiovascular disease in rheumatoid arthritis despite cardioprotective treatment: The 7-year prospective carre-study. (23rd January 2014) - van Sijl, A.M.; van den Oever, I.A.; Peters, M.J.; van Halm, V.P.; Smulders, Y.M.; Voskuyl, A.E.; Nurmohamed, M.T.
Abstract : Background: Rheumatoid arthritis (RA) is a chronic inflammatory joint disease which is associated with an increased cardiovascular (CV) risk. Still unknown is whether CV risk factors or the underlying inflammatory process in RA renders these patients more at risk of CV disease (CVD). An increment in these factors over several years might explain this predisposition. Objectives: The present study compared changes in these factors over time in RA-patients who did and did not develop CVD during follow-up. Methods: 7-year incidence rate of CVD was determined in a prospective cohort of 353 RA-patients. CV risk factors, RA-related factors and medication use were assessed at baseline, at 3-years and at 7-years of follow-up. Associations between the changes in investigated factors and development of CVD were assessed using generalized estimating equation (GEE) analyses. Results: After 7 years, there were 62 events over 2361 patientyears of follow-up, incidence rate (IR) of 26.3/1.000 patientyears. This was similar to the IR after 3-years of follow-up. GEE analyses showed that, during follow-up, changes in disease activity score of 28 joints (DAS28) and overall 10-year CV risk estimation (as calculated by SCORE) were associated with incident CVD. Use of biologics increased significantly in patients who did not develop incident CVD vs. those who did (26% vs. 6%), while use of statins increased significantly in patients who did develop incident CVD vs. those who did not (43% vs. 14%). Conclusions: An increased risk of incident CVD persists in patients with RA. Changes in both DAS-28 as well as 10-year CV risk estimation (SCORE) were associated with the 7-year CVD incidence. Cardioprotective treatment did not seem to extenuate this association. A more aggressive cardioprotective and anti-inflammatory treatment of RA might mitigate the burden of CVD in RA. Disclosure of Interest: None Declared